Two Student Perspectives on Clinical Medical Education During the COVID-19 Pandemic - Anne P. George; Elise E. Ewens (University Library System, University of Pittsburgh, 2021)
In the age of COVID19, the ultimate question in healthcare became who was essential and who was not. Basically, who could be cut from the roster in patient care? Unfortunately, as medical students, many of us did not make that cut, and as rotations were continually evolving and changing, students from even the same institution had varying experiences. Third-year clerkships are defined by the direct patient care and hands-on learning students get, but in the age of COVID19, "hands-on learning" has been a bit hard to come by. Hence, COVID has caused many changes in the way medicine is being taught and practiced. This article will detail the experiences of two medical students from the same institution, working in different locations for their third-year clerkships. We contrast our rural and urban experiences as students in the time of COVID and display the varying experiences students are having during this time. We touch on the potential ramifications for these wide varieties of experiences from students across the U.S. and how this will affect sub-internships and residency applications.